Student Awareness of the Implications of Political Geography Taught as a Subject at Geography Departments in Jordanian Public Universities - Abaalzamat, Khlaid Hamad (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to identify the extent to which geography department students understand concepts related to political geography. It also measures the relationship between their level of awareness of geographical concepts and the ability to understand study material and analyze events. Methods: The study relies on the descriptive survey method. The study population consists of all students studying geography at Jordanian public universities in the second semester of 2021-2022, while the study sample consists of (343) male and female students. Results: The study concludes that geography students’ level of awareness of concepts related to political geography is high, and the analysis shows that the subject of political geography contributes to a large degree in understanding geographical and political concepts. The study also demonstrates that there are no statistically significant differences in the level of geography students’ awareness of geographical concepts based on the university and the academic year. Furthermore, it concludes that there is a positive correlation between understanding academic subjects and geography students’ awareness of concepts related to political geography on the one hand, and between the contribution of political geography to students’ understanding of geographical and political concepts to analyze domestic and external events on the other. Conclusions: The researcher recommends developing the methods of teaching political geography courses at Jordanian universities, so that they are partly theoretical and partly practical, especially with regard to Jordanian national concepts.